ION BIOSORPTION Co ( II ) BY SEAWEED MACROSYSTIS PYRIFERA - Rabanal A., Melissa (2005)
The biosorption of Co(II) has been investigated using the brown seaweed Macrosystis pyfera, which contains principally algínate in its composition. The dry seaweed was crushed up to obtain three sizes of particle: less than 180, 180-250 y 250-500 µm, later was treated with a solution of 0.2 M of CaCl2 and was placed in a shaker for 24 hours at 150 rpm. The optimum pH of the process of biosorption was 5. The analysis was determinated by llame Atomic Absorption spectroscopy. The biosorption isotherms are described by Langmuir and Freundlich models. According to the pattern of Langmuir,the maximum capacities of biosorption qmax were: 47.85; 44.36 y 40 .16 mg/g for each size of particle respectively.